Multiport Converters Based EV Charging: Architectures, Challenges, Performance Analysis and Emerging Trends - Firdous Z.; Mekhilef S.; Mubin M.B.; Daula Siddique M.; Elsanabary A.; Ab Aziz N.F.; Seyedmahmoudian M.; Stojcevski A. (Institute of Electrical and Electronics Engineers Inc., 2024)
The increasing demand for electric vehicles has led to the need for efficient charging stations. Multiport converters have emerged as a solution for charging stations by integrating multiple energy sources and loads into a single converter, simplifying the system and improving power density. This comprehensive review paper analyzes multiport converters, focusing on their architecture, integrated topologies, challenges, future trends and comparison studies. The paper explores different power converter architectures and categorizes multiport converters based on isolation characteristics. It discusses the challenges and limitations of various types of multiport converters, including control complexity and voltage regulation. The paper also presents a comparative analysis of architectural and performance aspects. Overall, the paper provides valuable insights into multiport converters and their potential for efficient energy integration. 2023 IEEE.